Geochemical distribution and bioavailability of trace metals in sediments of the Bento Gomes River, Pocone - MT, Brazil - Santo Coringa, Josias do Espirito; Pezza, Leonardo [UNESP]; Oliveira Coringa, Elaine de Arruda; Santos Weber, Oscarlina Lucia dos (Inst Nacional Pesquisas Amazonia, 2016)
The sediment is one of the major compartments of aquatic ecosystems, it plays an important role in the transport and accumulation of metal. This study aimed to determine the concentration of metals in geochemical fractions of the Bento Gomes River sediments, Pantanal of Pocone (MT) through selective extraction and sequential in order to assess the distribution and mobility of metals. The sediments were collected in the rainy and dry seasons in eight different points, and the metals (Fe, Mn, Cr, Cu, Zn and Ni) extracted from sediments by sequential extraction procedures (based on the proposed by BCR protocol - Community Bureau of Reference) and selective extraction (based on the 3050B protocol of the Environmental Protection Agency of the United States), using certified reference materials for validation of the analytical method. All metals showed levels below the limits established by CONAMA Resolution no 454/2012 in the dry season, except for Ni in the rainy season (greater than 18 mg kg(-1)). The fractionation studies indicated that the metals were found in mobilized sediment fractions, especially associated with the iron oxides. The metals more mobile and hence more bioavailable, have been manganese, zinc and nickel, particularly in the rainy season. Largest copper contents were found in the residual fraction of the sediment, indicating low mobility in the aquatic environment. The sequence of mobility of the metals studied was Mn> Zn> Ni> Cr> Cu> Fe.
Keywords: Water resources; wetlands; sequential extraction